A severe presentation of chronic non-infectious osteomyelitis associated with ulcerative colitis: a case report - Alyssa Lorenze; Lukas Meadows; Temitope Kehinde; Cortney Ballengee Menchini (BMC, 2020)
Abstract Background Chronic Non-Infectious Osteomyelitis (CNO) is a chronic, relapsing, self-limiting inflammation of the bone. Although it is rare, CNO has been associated with inflammatory bowel disease and frequently precedes the initial diagnosis. We present a case of CNO in a patient with known ulcerative colitis in clinical remission who presented with purulent multifocal joint effusions in the setting of elevated inflammatory markers and fever suspicious for bacterial osteomyelitis. Case presentation Our patient is a 12-year-old girl with ulcerative colitis who presented with fevers and insidious onset of joint pain at multiple sites. She had multiple joint effusions on imaging and blood and joint cultures were negative. Biopsy of the left acromion demonstrated acute and chronic osteomyelitis with areas of necrosis and granulomatous inflammation suggestive of CNO. Patient was started on high dose corticosteroids as well as methotrexate injections with marked improvement in symptoms. Conclusion This case highlights that while purulent effusions are often indicative of bacterial osteomyelitis, the consideration of CNO in a patient with inflammatory bowel disease (IBD) with multifocal small bone involvement and negative blood cultures should be considered.